Labyrinthine sequestration secondary to auditory implantation: report of two cases and review of the literature. Issue 12 (11th December 2015) - Warner, E; Eze, N; Connor, S; Jiang, D
Abstract: Background: Auditory implantation into the inner ear is increasingly performed for a variety of indications. Infective complications are rare, but when they occur they can have devastating consequences. Case reports: This paper reports two cases where vestibular sequestration of the bony labyrinth developed following implantation into the middle ear. Conclusion: To the authors' knowledge, these are the first reported cases where vestibular sequestration has resulted from auditory implant surgery. This paper outlines the radiological changes characteristic of this pathology. It also describes the surgical and conservative treatment options for this condition, challenging the previously accepted belief that affected patients always require aggressive surgical intervention.